PENGARUH KONFLIK, KOMUNIKASI, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA TIM KERJA RSUD CEMPAKA PUTIH - Lenni Ambriani; Koentari Koentari (Sekolah Tinggi Ilmu Ekonimi IPWI Jakarta, 2020)
Conflict, communication, and leadership style are the three factorsto influence teamwork perfomance on the RSUD Cempaka Putih Jakarta. This research aimed to determine the effect of conflict, communication, and leadership style toward teamwork performance on the RSUD Cempaka Putih Jakartaby taking 69 employees from 5 teamwork as the research sample, calculated using the Slovin formula of the total population of 219 employees at the margin of error of 10%. Data were collected by questionnaire instruments covered by the five rating scale. Quantitive research was conducted by describing and analizing research data. The multiple linier regression analysis are the statistic approach to data analysis. Hypothesis testing is done by t-test and F-test.The study produced four major findings consisten with the hypothesis put forward by Y = 10.941 + 0.298X1+ 0.475X2 + -0.057X3, that are: 1) Conflict has a positive and significant influence on teamwork performance by b1 = 0.298 and sig. t = 0.006 < 0.05; 2) Communication has a positive and significant influence on teamwork performanceb2 = 0.475 dan sig. t = 0.000< 0.05; 3) Leadership style has a negative and not significant influence on teamwork performanceb3 = -0.057 dan sig. t = 0.635 > 0.05; 4) Conflict, communication, and leadership style simultaneously has a positive and significant influence on teamwork performance by constanta value a = 10.941 and sig. F = 0.000.Base on the research finding, in order to increase teamwork performance can be done by increase conflict management, communication, and leadership style. Key words:Conflict, Communication, Leadership Style, Teamwork Perfomance